The construction and testing of a multi-mode scanning confocal and atomic force microscope - Vanhouse, Russell Edward (2020)
At the University of Nottingham, two research groups fabricate atom chips and hexagonal boron-nitride (h-BN) devices. These prototypes require characterisation to provide information about their functionality to the researchers. Electroluminescence and photoluminescence data is required of h-BN devices, atom chips and spintronic devices require measurement of their magnetic field strength. An instrument capable of performing this would be similar in design to a nitrogen-vacancy (NV−) magnetometer. The requirements of this instrument that differ from others are that it should accept larger samples, scan over a larger range, function in ambient conditions and be highly flexible with regards to the types of measurements it can perform. The aim of my studies was to construct such an instrument, capable of imaging the surface of samples whilst measuring reflectance, photoluminescent and electroluminescent emission and measuring the surface topography with an AFM probe, whilst probing the sample with microwaves and a DC magnetic field. The resultant instrument should also be suitable to convert into an NV− magnetometer. This thesis describes the equipment selected and the construction. Functionality is demonstrated by performing tests on samples of nanodiamonds and h-BN devices. The tests provide information about the electroluminescent and photoluminescent properties of these devices which has added to the understanding of how they work. A photoluminescence source was located on one h-BN device, coupled with the knowledge of how it was fabricated, this demonstrates that photoluminescence is also observed in samples of very high purity. Electroluminescence was detected and located on a different device, the instrument confirmed the origin of the emission, in a region of overlap between two thin flakes of h-BN. It also showed that heat generated by the tunnelling current caused deformation of the layers, resulting in a bulge on the surface. The instrument investigated thin flakes of h-BN, to use the information in conjunction with data taken with an imaging ellipsometer. This ellipsometer is unique in its ability to probe samples with 6.5 eV photons, it is used to measure h-BN at and above its band gap. A model is fitted to the data, which gives the refractive indices of h-BN. The results indicate a birefringence of ∆n=2.2 at 6 eV, making h-BN one of the most birefringent materials recorded. To summarise, the instrument has been proven to be functional and flexible. It is suitable to be used as an NV− magnetometer when an appropriate nanodiamond is located and it has provided information on the h-BN devices and aided in the discovery of new information about h-BN as a material.